Is the Combination Nirmatrelvir Plus Ritonavir Effective for Treating or Preventing COVID-19? - article Editorial (Безопасность и риск фармакотерапии, 2022)
This article is the Russian translation of the Plain Language Summary (PLS) of the Cochrane Review previously published in the Cochrane Database of Systematic Reviews. Original publication: Reis S, Metzendorf M-I, Kuehn R, Popp M, Gagyor I, Kranke P, et al. Nirmatrelvir combined with ritonavir for preventing and treating COVID-19.Cochrane Database of Systematic Reviews 2022, Issue 9. Art. No.: CD015395. https://doi.org/10.1002/14651858. CD015395.pub2